(untitled) (The Pakistan Development Review, 1985)
This paper is a straightforward exercise in estimating earnings functions and computing the private rates of returns to different levels of education. The latter summarizes the incentives to the individual to invest in human capital formation, while the former helps in ascertaining the influence of both human and non human capital variables on the earnings of the individual. A few studies conducted in the past found the rates of returns to education in Pakistan not in conformity with those of the majority of the developing countries for which such estimates exist. The estimated rates were lower for all levels of education in Pakistan than in the developing world. Moreover, the computed rates of returns had a positive association with the level of education.